"Alle 600 Jahre kam der deutsche Geist sozusagen wieder dran": deutsche Sprachgeschichte - Versgeschichte - Literaturgeschichte - Knapp, Fritz Peter (De Gruyter, 2018)
Abstract: Theodor Vennemann’s hypothesis 1995 proposing an impact of prosodic change on German versification has not been taken enough into consideration by literary historians up to this day. The best evidence of this impact can be found in the usage of masculine dissyllabic ending in Middle High German strophes, which is provable occasionally till the fourteenth century, but obliterated gradually in the different dialects of the ›theodisc‹ area already since the twelfth century in different speed, but not always according to the very speed linguists found out for the lengthening of short vowels in the open syllable. But the crash of the MHG versification postulated by Vennemann is quite confirmed. Replacing it with the Latin-Romance principle of counting syllables does not help really, but causes only confusion until the reform of versification combines it with strict alternation of lift and dip. Only this new beginning permits, but not earlier than during the eighteenth century, again a blossom of verse poetry as at the end of the twelfth century.
Aus: Beiträge zur Geschichte der deutschen Sprache und Literatur, 137 (30 November 2015), Nr. 4. pp. 599-622. ISSN 1865-9373